Between man and man - Buber, Martin, 1878-1965 (Routledge classics., 2002)
Martin Buber believed that the deepest reality of human life lies in the relationship between one being and another. Between Man and Man is the classic work where he puts this belief into practice, applying it to the concrete problems of contemporary society. Here he tackles subjects as varied as religious ethics, social philosophy, marriage, education, psychology and art. Including some of his most famous writings, such as the masterful 'What is Man?', this enlightening work challenges each reader to reassess their encounter with the world that surrounds them.